Development Of Webcomic Learning Media Of Website Materials In XI Class Of Online Business And Marketing - Raya Sulistyowati; Tri Sudarwanto2; Indy Astira Kause Putri3 (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2019)
The digital age has fierce competition for schools to prepare students, especially in the cognitive aspects. The facts found in the potential and problems show that there are still many students who do not understand the material in Evaluating Website Basic Competencies. The purpose of this study was to determine the development process, the feasibility of the media and students' responses to webcomic learning media. The study chose the 4D research model adapted from Thiagarajan (1974) using data collection techniques in the form of observations and questionnaires. The research subjects were taken as many as 8 people (limited test) and 20 people (field test) in XI class of Online Business and Marketing. The results of the evaluation of the validators had a presentation of 87%. Furthermore, the trial phase was limited to a percentage of 85%, at the trial stage a large percentage of 92%. Increasing the percentage of students' responses can be one of the references that webcomic learning media is worthy of being one of the supporting learning media when learning takes place.